The Implementation of Halal Network Indonesia (HNI) Business Among Muslim and Non-Muslim Communities - Abdillah Mundzir; Aminatuz Zukhriyah; M. Sulhan (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2024)
This research aims to describe the assumptions of mountain communities (Tosari and Nongkojajar) in using Halal labeling products (HNI) during the pandemic. The research design employed in this study is quantitative descriptive research with an associative or relational approach. Data collection techniques utilized research instruments, and the data analysis is quantitative/statistical, with the objective of testing the predetermined hypotheses. The researcher determined a sample size of 65 individuals using the Slovin formula, who then became one of the research targets for obtaining several data points. The research findings indicate that both non-Muslim and Muslim communities in Tosari and Nongkojajar generally prefer HNI for their daily needs and health due to the sense of security and high trust placed by the community in the HNI halal label. The implications of this research extend to the development of the local economy, the creation of sustainable business models, and the formulation of policies for the government.